2012
DOI: 10.1073/pnas.1202984109
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific targeting dissociates the therapeutic from the adverse effects of protein kinase inhibition in allergic skin disease

Abstract: The kinase p38α, originally identified because of its endotoxinand cytokine-inducible activity and affinity for antiinflammatory compounds, has been posited as a promising therapeutic target for various immune-mediated disorders. In clinical trials, however, p38α inhibitors produced adverse skin reactions and other toxic effects that often outweighed their benefits. Such toxicity may arise from a perturbation of physiological functions unrelated to or even protective against the disease being treated. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Importantly, despite the diversity of cell types where p38 MAPK plays a role, its effects in all of the cell types studied to date in EAE are unidirectionally propathogenic. This is in contrast to other immune-mediated models of inflammation, where emerging evidence points to potential anti-inflammatory roles for this kinase (62)(63)(64), which may explain the lack of efficacy of p38 MAPK inhibitors in treating rheumatoid arthritis (RA) and Crohn's disease (see below).…”
Section: Conclusion and Potential Therapeutic Perspectivesmentioning
confidence: 74%
“…Importantly, despite the diversity of cell types where p38 MAPK plays a role, its effects in all of the cell types studied to date in EAE are unidirectionally propathogenic. This is in contrast to other immune-mediated models of inflammation, where emerging evidence points to potential anti-inflammatory roles for this kinase (62)(63)(64), which may explain the lack of efficacy of p38 MAPK inhibitors in treating rheumatoid arthritis (RA) and Crohn's disease (see below).…”
Section: Conclusion and Potential Therapeutic Perspectivesmentioning
confidence: 74%
“…Nevertheless, the involvement of the non‐epithelial cell‐derived p38δ in skin tumorigenesis cannot be excluded, since p38δ is expressed in many cell types, including immune, endothelial, and mesenchymal cells (reviewed in ), interplay of which with epithelial cells is known to be of key importance for tumor development and progression . Importantly, studies targeting p38α isoform in distinct cell types have revealed cell type‐specific effects of p38α loss on inflammatory and allergic responses in skin, and on inflammatory bowel disease . The effects of keratinocyte‐specific and myeloid cell‐specific p38δ loss on distinct stages of chemical skin carcinogenesis are under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CKO studies have shown that deletion of p38a in different cell types can have opposing effects on inflammation and disease outcome [17,[19][20][21]. In fact, deletion of p38a in macrophages/ myeloid cells aggravated skin inflammation [17,20] and experimental arthritis [18]. Moreover, we have shown in a mouse model of MS, an autoimmune inflammatory disease of the CNS-that deletion of p38a in myeloid cells can either exacerbate or ameliorate disease in a sex-specific fashion [22].…”
Section: Introductionmentioning
confidence: 86%
“…Taken together, these results suggest that cell-specific targeting of p38a in myeloid cells may have therapeutic potential in treating colitis and possibly other inflammatory diseases, particularly if combined with restoration of IL-10 levels. In contrast, deletion of p38a in myeloid cells can aggravate skin inflammation [17,20], experimental arthritis [18], and autoimmune CNS inflammation [22], suggesting that perhaps protective functions of myeloid p38a are colitis specific. This notion is supported by the exquisite sensitivity of colitis to the absence of IL-10 and the critical requirement for IL-10 to maintain normal intestinal homeostasis [50,53,54].…”
Section: Deletion Of Myeloid P38a In the Absence Of Il-10 Is Protectimentioning
confidence: 99%
See 1 more Smart Citation